2021
DOI: 10.1021/acs.jpca.1c07412
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determination and Bonding Properties of Gas-Phase Ternary [O, Ta, 2C] Anions

Abstract: A combined anion photoelectron spectroscopic and quantum chemical investigation was performed to explore the structures and bonding properties of ternary [O, Ta, 2C] − anions. The atomic bonding connectivity of the ternary anion was found to be (O−Ta−C 2 ) − rather than (Ta−O−C 2 ) − . The photoelectron spectrum using 266 nm photons was measured, and the theoretical simulated spectrum was calculated, with good agreement between experimental and theoretical results being found. Computations obtained electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The study revealed that the geometries of Ta 2 Si n clusters with silicon atoms ranging from 11 to 18 undergo a transformation from a tubular shape to a cage structure and eventually to a fused cage configuration. 32 Our previous work utilized anion photoelectron spectroscopy and quantum chemistry calculations to explore Ta 1−3 Si 12 ̅ /0 , 33 Ta 2 Si 2−21 ̅ /0 , 34,35 TaSi 2−15 ̅ /0 , 36 and TaSi 16 ̅ /0 clusters. 37 While the photoelectron spectrum of TaSi 17 ̅ has been documented, 24 study, we investigate the structures and chemical bonding of TaSi 17 ̅ /0 and TaSi 18 ̅ /0 clusters by using anion photoelectron spectroscopy and theoretical computations.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that the geometries of Ta 2 Si n clusters with silicon atoms ranging from 11 to 18 undergo a transformation from a tubular shape to a cage structure and eventually to a fused cage configuration. 32 Our previous work utilized anion photoelectron spectroscopy and quantum chemistry calculations to explore Ta 1−3 Si 12 ̅ /0 , 33 Ta 2 Si 2−21 ̅ /0 , 34,35 TaSi 2−15 ̅ /0 , 36 and TaSi 16 ̅ /0 clusters. 37 While the photoelectron spectrum of TaSi 17 ̅ has been documented, 24 study, we investigate the structures and chemical bonding of TaSi 17 ̅ /0 and TaSi 18 ̅ /0 clusters by using anion photoelectron spectroscopy and theoretical computations.…”
Section: Introductionmentioning
confidence: 99%